The problem of supporting and growing small and medium enterprises in ‎Algeria. Reality, limitations and challenges‏ ‏ - Sherif, Ismail; Salemi, Rachid (Dirassat Journal Economic Issue, 2020)
The implementation of the new industrial policy has led the public authorities to associate small and medium-sized enterprises or economic and social development, the scope of which will gradually lead to the emergence in our country of a competitive industrial fabric on a regional scale and international. This contribution on our part will lay out a roadmap for a diagnosis of the various major axes of the development strategy of MSEs in Algeria, as well as the analysis of the realities and constraints that prevent these companies from creating wealth and jobs.